My analysis with Blanton. To the roots of American poetry therapy (Altre Modernità, 2024)
The roots of poetry therapy are geographically and temporally difficult to find, even though it is in the US that poetry therapy has drawn most of the attention. A pivotal role, in this sense, was exerted by the psychiatrist Smiley Blanton (1882-1966), also known for the journal of his analysis with Sigmund Freud. Blanton habitually used poetry therapy with his patients and, also thanks to the aid of previous studies, he managed to sanitize it from its most obvious naive elements. Today, poetry therapy is widely practiced, and it is a hope for the future to promote a thicker dialogue between it and the neurosciences as a whole.
Keywords: Smiley Blanton; poetry therapy; The United States of America; neurosciences